PEMANFAATAN INSTAGRAM OLEH PERPUSTAKAAN PTKIN DI JAWA TIMUR - Fiqru Mafar (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
The object of this research is to investigate the Instagram usage in the PTKIN Library in East Java. The method in this research uses a case study model through content analysis of the post on the seven PTKIN Library Instagram accounts in East Java. The analysis is carried out by analyzing account ownership, growth of Instagram accounts, posting activity, and their use in each PTKIN Library Instagram account in East Java. The research data was taken on the same day, December 5, 2020. The results showed that generally Instagram has been used by PTKIN library managers in East Java. This can be seen from the account ownership by the entire library. Based on its growth, Instagram was only used by the PTKIN library manager in East Java in 2017. The average posting activity for each account was 130.28 posts. The use of Instagram by the PTKIN library is mostly used as a marketing/ promotion medium, amount to 560 posts or 61.40%. Meanwhile, the use of Instagram that is still rarely done is requesting input / suggestions from users, which is 5 posts or 0.55% of all posted content. As a suggestion, librarian need to optimize the use of Instagram to capture suggestions from library users.